Analyze Ability of Early Childhood Based on Gender - Tanjung, Salsabila Hasiana; Suparno, Suparno (Muhammadiyah University Prss, 2019)
The experimental design in this study has a particular interest in making conclusions made about gender differences in the ability to analyze children aged 5 years in the perspective of Taxonomic Bloom. The problem in this research is represented by the sample of research subjects by using items that have been loaded instrument. Test reliability and heterogeneity of variance can be randomly drawn conclusions from the scores of women and men on the instrument used. The results showed a statistically significant effect size difference difference (.01 Mean) in favor of women. The magnitude of gender differences in the impact of learning outcomes, however, differs substantially throughout the specific product domain graphically.